Palliative Care in Patients with Liver Cirrhosis: A Scoping Review of Identification, Interventions, and Implementation Barriers and Facilitators - Birgitte Gade Jacobsen; Mai-Britt Guldin; Mette Munk Lauridsen; Lea Ladegaard Grønkjær (Healthcare, 2026)
Background/objectives: Liver cirrhosis is a life-limiting, non-malignant condition with a high symptom burden, psychosocial challenges, and unpredictable disease trajectory. As such, patients with cirrhosis and their caregivers might benefit from palliative care (PC) interventions. However, in most clinical settings, PC is not yet an integral part of basic hepatology care. This scoping review aimed to map how patients with cirrhosis are identified for palliative care, which interventions are delivered, and which factors influence implementation. Methods: The review was conducted in accordance with Joanna Briggs Institute methodology and reported following the PRISMA-ScR guidelines. PubMed, CINAHL, and Scopus were searched. The initial search was conducted in November 2024 and updated in December 2025, June and August 2026. Quantitative, qualitative, and mixed-method studies involving adults (≥18 years) with liver cirrhosis, informal caregivers, and healthcare professionals were included. Data were charted descriptively and organized according to identification approaches, interventions, barriers, and facilitators. Results: In total, 39 studies were included. Patients were identified using identification tools, screening tools, clinical criteria, and prognostic scores. Interventions across inpatient, outpatient, and home-based settings included symptom management, prognostic communication, advance care planning, goals-of-care discussions, psychosocial support, and multidisciplinary collaboration. Overall, studies reported improvements in symptom management, communication, healthcare utilization, and informal caregiver outcomes. However, palliative care integration remained inconsistent and often occurred late. Key barriers included prognostic uncertainty, fragmented care pathways, limited training, and misconceptions about palliative care. Facilitators included education, structured assessment tools, and integration of palliative care into hepatology services. Conclusions: This review identified diverse approaches to patient identification and palliative care delivery, alongside key barriers and facilitators to implementation. Earlier integration of palliative care based on care needs, supported by communication, education, and interdisciplinary collaboration, may improve care for patients with cirrhosis.